Test To Physical Condition Parameters: For The Football Athletes Persik Kediri Under – 20 At 2020 - Nur Ahmad Muharram; Slamet Junaidi; Sugito; M. Anis Zawawi; M. Akbar Husein Allsabah (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2020)
The purpose of this parameter test is to equip persik trainers with themselves and their staff in order to know the physical condition of the U-20 persik kediri athlete so that the training program can be on target. In addition, the parameter test is also used to evaluate the progress of training towards achievement in each match. This parameter test also has the benefit of setting methods for preparing parameter tests and compiling test guidelines, or SOP so that parameter tests carried out in the field have valid and reliable test prerequisites, and have the same interpretation throughout Indonesia, especially in the Football Sports Branch . For the method here, it uses the field practice method through the persik kediri athlete U-20 to carry out a series of parameter tests in soccer Athletes are asked to carry out the test series in accordance with SOPs that have been determined. The results of this parameter test are that the persik kediri athlete U-20 has physical conditions in categories or good norms in each form of test that is directed at the physical condition of soccer athletes